THE EFFECTIVENESS OF TRAINING TOWARDS JOB SATISFACTION WITH JOB PERFORMANCE AS A MEDIATING VARIABLE AT AGRICULTURAL AGENCY: EVIDENCE FROM MALAYSIA - Nurul Muniroh Basir; Sentot Imam Wahjono (BALANCE: Economic, Business, Management and Accounting Journal, 2014)
The aim of this research is to study the effectiveness of training towards job  satisfaction with  job  performance as  mediating  variable.  This  research conducted by Qualitative approach with Path Analysis. The population of this research are  1,597  employees in  Muda  Agricultural Development Authority (MADA),   Kedah,   Malaysia.   310   sets   of   questionnaires   distributed   to respondents and 222 are collected back for analysis with SPSS. This research found that Job Satisfaction influence by Training directly or through by Job Performance, but better through by. These research findings have theoretical implications that the effectiveness og the employee’s job performance after training should be through the achievement of job satisfaction first.Training,  job  performance,  job  satisfaction,  Muda  Agricultural  Development Authority (MADA) Malaysia.Structure, Growth Rate, Profitability, Cash Flow and Firm Size